2021
DOI: 10.1063/5.0045190
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Raman spectra and color of tungsten trioxide (WO3) thermally evaporated from a tungsten filament

Abstract: The color exhibited by tungsten trioxide (WO3) can be associated with both its stoichiometry and crystallinity. Correlation between the color exhibited by WO3 powders and their purity and crystalline properties is reported in this paper. The WO3 powders were deposited by evaporation of tungsten trioxide from the surface of a tungsten filament. The WO3 powders exhibited three different shades of blue: navy, royal, and sky. The color of the WO3 powders changed to white after thermal treatment at 500 °C for 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…56−60 The Raman stretch at 318 cm −1 can also be attributed to a monoclinic bending mode. 56 The Raman vibrations appear to be broader and shifted to lower wavenumbers as compared to the tungsten oxide films and larger structures. 58,61 This is due to the distortion in the overall crystal lattice resulting from oxygen vacancies that reduces the crystallinity compared to larger bulk-like structures.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…56−60 The Raman stretch at 318 cm −1 can also be attributed to a monoclinic bending mode. 56 The Raman vibrations appear to be broader and shifted to lower wavenumbers as compared to the tungsten oxide films and larger structures. 58,61 This is due to the distortion in the overall crystal lattice resulting from oxygen vacancies that reduces the crystallinity compared to larger bulk-like structures.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The Raman spectrum of as-synthesized NPLs includes distinct monoclinic tungsten oxide vibrational modes (Figure B, black line). These peaks are assigned as the crystal lattice vibration of (W 2 O 2 ) n chains at 71 cm –1 , W–O stretch at 123 cm –1 , bending vibration of (O–W–O) at 252 cm –1 , and (O–W–O) stretches of the WO 6 octahedra at 692 and 797 cm –1 . The Raman stretch at 318 cm –1 can also be attributed to a monoclinic bending mode . The Raman vibrations appear to be broader and shifted to lower wavenumbers as compared to the tungsten oxide films and larger structures. , This is due to the distortion in the overall crystal lattice resulting from oxygen vacancies that reduces the crystallinity compared to larger bulk-like structures .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Structural analysis by Raman provides similar results indicating no change in ligand treatment (Figure C). All ligand-treated samples contain characteristic oxygen-deficient crystal lattice vibration-related peaks, marked by dashed lines at 803, 668, and 233 cm –1 . Raman spectroscopy is known to be sensitive to subtle surface binding changes and the position of Raman vibrational stretches could vary depending on the sampling deposition technique. As illustrated in Figure C, depending on the type of ligand used to passivate the surface of WO 3– x NPLs, we observe a slight shift in the peak position in Raman spectra, which can be attributed to the changes in the film morphology, as well as electronic interactions between ligands and NPLs. , As described above, we showed that phosphonate and carboxylate binding head groups form different bonding interactions with WO 3– x NPLs.…”
Section: Resultsmentioning
confidence: 99%
“…of Zn(Cy) 2 to the yellow suspension of WO 3 •2H 2 O in toluene, it quickly turns green, indicating the reaction of the zinc precursor with the NLs. The color change is ascribed to the formation of W n+ (n < 6) species associated with the presence of oxygen vacancies [35,36]. This suggests that the oxophilicity of Zn 2+ ions of the precursor is strong enough to remove oxygen atoms from the WO 3 lattice and yield the first surface germs of ZnO.…”
Section: Synthesis Of Zno@wo3 Nanocomposite By Reaction Of Wo3•2h2o W...mentioning
confidence: 99%